A life prediction model coupled with residual stress and initial damage on aerofoil specimens subjected to foreign object damage. (January 2022) - Hu, Dianyin; Yan, Lin; Mao, Jianxing; Guo, Xiaojun; Shan, Xiaoming; Wang, Rongqiao
Highlights: Mechanism of fatigue failure after FOD is investigated using SEM observations. 3D FEA is conducted to achieve the stress state after impact and during fatigue loading. A novel theory of critical distance method coupling residual stress and initial damage is proposed and validated. Abstract: Foreign object damage (FOD) has been identified as one of the main concerns for fan blades. In this paper, systematic experimental and numerical investigations are conducted on aerofoil specimens subjected to FOD by a falling object. The failure mechanism is attributed to the combination of stress concentration, residual stress, and initial damage. Finite element analysis is carried out to simulate the stress field. Using the experimental data from smooth, typically notched, and FOD notched specimens, a novel theory of critical distance model coupling residual stress and initial damage is proposed, falling in a scatter band of 2.